DEVELOPMENT OF FABRIC-BASED 3D MICROFLUIDIC COMPARTMENT AS A SAMPLE CONTAINER FOR ANALYTE DETECTING SYSTEM - Yusreza Irsyan, Muhammad
Until now, the most general body substance level monitoring techniques in the diagnostic field still involve drawing patients’ blood in the process. In the case of diabetes mellitus, patients need regular and frequent instances of blood glucose level monitoring so that means there is a need for a technique which keeps the patients’ comfort by using different analyte instead of blood. Besides, techniques such as selfmonitoring blood glucose (SMBG) and continuous glucose monitoring (CGM) are requiring a lot of body fluid samples, accumulatively, to compensate the accuracy and efficiency of the technique. Researchers had investigated the usage of different analytes instead of blood such as urine and sweat with small amount of analyte required to run the operation. However, the techniques to fabricate the sample collecting devices are complex and costly. In this study, we developed a fabric-based 3D microfluidic device as a sample container for analyte detecting system. The device was fabricated using wax transfer technique with batik wax as a hydrophobic barrier to stop the sample from wicking around the fabric. The device is a 3D chip formed by folding the fabric with transferred wax patterns which formed a well-like container area. The device contained 39.41 µL of the sample for more than one hour with a capacity error mean of 4.24%. The device also preserved its functionality with a success rate of 86.2% from extreme deformation of folded by 180° and twisted by 90°.